2016
DOI: 10.1103/physreva.93.063408
|View full text |Cite
|
Sign up to set email alerts
|

Autoionization in time-dependent density-functional theory

Abstract: We compute the exact exchange-correlation potential of the time-dependent density functional theory (TDDFT) for the correlated process of autoionization. The potential develops barriers which regulates the autoionization rate. TDDFT employing known and practicable exchange-correlation potentials does not capture any autoionization dynamics. Approximate exchange-correlation potentials capturing such dynamics would necessarily require memory effects and are unlikely to be developed as will be illustrated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 32 publications
0
13
0
Order By: Relevance
“…In particular, Auger transitions are not expected to be accounted for. [22,23] However, this is not a major restriction in case of the present simulations, because Merino et al [24] have concluded from their study using a model Hamiltonian that at the low H + kinetic energies considered here (below keV) the charge transfer is dominated by resonant processes. Finally, we note that the TDDFT-MD simulations we present below refer to the valence electrons only.…”
Section: Tddft Simulations Of Charge Transfer and Ion Stoppingmentioning
confidence: 84%
See 2 more Smart Citations
“…In particular, Auger transitions are not expected to be accounted for. [22,23] However, this is not a major restriction in case of the present simulations, because Merino et al [24] have concluded from their study using a model Hamiltonian that at the low H + kinetic energies considered here (below keV) the charge transfer is dominated by resonant processes. Finally, we note that the TDDFT-MD simulations we present below refer to the valence electrons only.…”
Section: Tddft Simulations Of Charge Transfer and Ion Stoppingmentioning
confidence: 84%
“…[30] It is argued that no electron-electron relaxation (Auger effect) occurs when the present adiabatic XC-functionals are employed. [22,23] Theoretical work on the He + /Al system shows that in case of the projectile velocity range applied here, the Auger channel is the relevant one in order to be able to describe the experiment. [52][53][54][55] First test calculations within the framework described above for a He + ion (E kin = 2 H) incident on an Al(111) surface, confirm that Auger processes do not show in the calculations performed using an adiabatic GGA XC-functional.…”
Section: 2mentioning
confidence: 92%
See 1 more Smart Citation
“…182, when applying the ALDA for the XC potential in TDDFT doubly excited configurations are not accounted for. Based on the calculation of an exact XC-potential, V. Kapoor [183] has concluded that autoionization requires inclusion of memory effects in the XC-potential, which displays a rather complicated structure. When calculating e.g.…”
Section: B Time-dependent Dftmentioning
confidence: 99%
“…The described grid is partitioned into different sections, figure 1(a). This partitioning technique has been successfully implemented previously in several theoretical studies of the ionization from the ground state of small atoms and molecules [32][33][34][35][36][37][38]. Time-dependent changes in the electronic density in each of the grid segments, I to IX in figure 1(a), indicate dynamical effects caused by the interaction with an external laser field.…”
Section: P Gmentioning
confidence: 99%